Analisis Faktor Risiko Malaria di Asia Tenggara - Devi Ayu Rokhayati; Raniand Cucuomi Putri; Nabila Allaeyda Said; Dwi Sarwani Sri Rejeki (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
Malaria is a disease caused by the parasites of the genus Plasmodium, which are transmitted by the bite of the female Anopheles mosquito. All tropical countries, including Southeast Asia, reported malaria cases. Several factors related to human behavior and the environment in which people live cause the incidence of malaria. The objective of this study was to analyze the risk factors for malaria in Southeast Asia and determine which risk variables had the greatest impact on the prevalence of malaria. This study is a review of the literature with a narrative review model using English and Indonesian journals from 2017 to 2021. The journals were obtained through the health journal provider databases Pubmed, Google Scholar, ScienceDirect, Researchgate, and Academic.edu. Malaria risk factors in Southeast Asia are influenced by behavioral and environmental factors. Behavioral factors include not use of mosquito nets, being active at night, male gender, and risky work. Environmental factors include rural areas, open-access dwellings, housing near cattle pens, and proximity to mosquito breeding sites. Changes in human behavior to avoid mosquito contact and environmental control are required to reduce the incidence of malaria.